2017
DOI: 10.18632/oncotarget.17586
|View full text |Cite
|
Sign up to set email alerts
|

IRF5 is elevated in childhood-onset SLE and regulated by histone acetyltransferase and histone deacetylase inhibitors

Abstract: Interferon regulatory factor 5 (IRF5) plays a critical role in the induction of type I interferon, proinflammatory cytokines and chemokines, and participates in the pathogenesis of autoimmune diseases such as systemic lupus erythematosus (SLE). However, the relationship between IRF5 and childhood-onset SLE remains elusive. In the present study, we demonstrated that levels of mRNA expression of IRF5, IFN-α, and Sp1 were significantly increased in childhood-onset SLE, as seen on quantitative real-time PCR, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…In the case of SLE, GWAS across multiple ancestral backgrounds have confirmed that IRF5 polymorphisms associate with SLE risk [( 60 , 63 66 )]. In SLE patient blood, IRF5 expression and activation were found to be significantly elevated ( 67 71 ). Prior to these findings, IRF5 was identified as a critical mediator of MyD88-dependent TLR signaling, leading to the expression/production of multiple pro-inflammatory cytokines including type I IFNs, IL6, TNFα, IL12, IL23, and others implicated in autoimmune disease pathogenesis ( 62 , 72 76 ).…”
Section: Implications For Irfs In Disease Pathogenesis–why Target Thementioning
confidence: 99%
“…In the case of SLE, GWAS across multiple ancestral backgrounds have confirmed that IRF5 polymorphisms associate with SLE risk [( 60 , 63 66 )]. In SLE patient blood, IRF5 expression and activation were found to be significantly elevated ( 67 71 ). Prior to these findings, IRF5 was identified as a critical mediator of MyD88-dependent TLR signaling, leading to the expression/production of multiple pro-inflammatory cytokines including type I IFNs, IL6, TNFα, IL12, IL23, and others implicated in autoimmune disease pathogenesis ( 62 , 72 76 ).…”
Section: Implications For Irfs In Disease Pathogenesis–why Target Thementioning
confidence: 99%
“…In PBMCs from patients with jSLE, mRNA expression of IRF5, IFN-α and Sp1 is increased. Exposure of cells to HDAC (histone deacetylase) inhibitor TSA (trichostatin A) or forced histone acetylase p300 expression repressed IRF5 promoter activity, suggesting the use of HDACi (HDAC inhibitor) as a potential future therapeutic option in SLE [ 109 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also involved in adaptive and innate immunity. The first identified single-nucleotide polymorphism (SNP) in IRF5, Rs2004640, is closely related to the high expression of several IRF5 isoforms and is a valuable genetic risk factor for SLE (23).…”
Section: Discussionmentioning
confidence: 99%